PENJATUHAN SANKSI PIDANA DIBAWAH BATAS MINIMUM ANCAMAN HUKUMAN BAGI ANAK PELAKU TINDAK PIDANA NARKOTIKA - Amru Eryandi Siregar; Madiasa Ablisar; Mahmud Mulyadi; Marlina Marlina (Universitas Sumatera Utara, 2017)
ABSTRACT Some of the reasons decided by penalties ½ (half) of the amount of the minimum sanction of imprisonment is based on Article 22 No. 3 of 1997 on Juvenile Justice, which is